Letter to Jane Tolmach from Marcia Herman and Mary Aidlin - Marcia Herman::::::; Mary Aidlin:::::: (1976)
In a June 28, 1976 letter from the organization Women For, Jane Tolmach is congratulated on the successful results of the June 8th election. The Politics Committee chairpeople, Marcia Herman and Mary Aidlin, express their continued support for her campaign. They affirm their commitment to helping secure her victory in the upcoming November election.